IMPROVING THE QUALITY SERVICE OF TOUR GUIDES THROUGH THE COMPETENCY CERTIFICATION PROGRAM - Rahmawati, Ema (Proceeding SENDI_U, 2015)
The tourism development is expected to get the full support of the tourism stakeholders like the Government, theprivate sector, the public sector including tourists. The tourist guides as one of the stakeholders as someone who isin charge of providing guidance, information and hints about things to see and help everything that touristâs needed.A tour guide as well as a front liner and also as an information agent need to get special attention. Globalizationera requires manpower in the tourism sector have a competency certificate based on The Indonesian Standard ofCompetence of National Work (SKKNI). Of the many components of the stakeholders, the tour guide is the mainthing as someone who directly to the tourist, therefore need coaching and more intensive development. Professionalcertification is one mechanism used to assist in maintaining and improving professional or technical competence innumerous professions. It can potentially be used to assist in improving tour guide performance and raising andmaintaining guiding standards. Competency certification program is able to improve the quality of the tour guide inorder to provide better service quality improvement services. In tourism industry, its certification program tobecome an important part in the development of tourism. Certificate of competence give pride for who gets it,because it makes them more confidence on their job. With a certificate of competence their have bargaining powerfor salaries and quality of work are increasing. For the tourism company, the tour guide who have certified thecompetency is an asset in business competition. Therefore mutually beneficial solutions between the tourismcompany and the tour guide need to be grown.Keywords: Improving quality of the tour guide,Sertification competency of tour guide